New developments implicating IL-21 in autoimmune disease. Issue 122 (August 2021) - Ren, Heather M.; Lukacher, Aron E.; Rahman, Ziaur S.M.; Olsen, Nancy J.
Abstract: Elevated interleukin (IL)-21 is a common finding in the tissues and/or sera of patients with autoimmune disease. CD4 T cells are the primary producers of IL-21; often the IL-21 producing CD4 T cells will express molecules associated with follicular helper cells (TFH ). Recent work has shown that the CD4 T cell-derived IL-21 is able to promote effector functions and memory differentiation of CD8 T cells in chronic infections and cancer. Autoimmunity has similarities to chronic infections and cancer. However, CD4 T cell-derived IL-21:IL21R signaling in CD8 T cells has not been fully appreciated in the context of autoimmunity. In this review, we assess the current knowledge regarding CD4 T cell-derived IL-21 and IL21R signaling within CD8 T cells and evaluate what implications it has within several autoimmune diseases including systemic lupus erythematous, rheumatoid arthritis, juvenile idiopathic arthritis, type 1 diabetes mellitus, psoriasis, Sjögren's syndrome, vitiligo, antiphospholipid syndrome, pemphigus, and giant cell arteritis. Highlights: Elevated serum and/or tissue interleukin-21 is associated with autoimmune disease. Follicular helper-like CD4 T cells are often the sources of IL-21 in the tissues. CD8 T cells respond to IL-21 in ways that may further drive autoimmune disease. Targeting IL-21:IL21R signaling may offer patients with autoimmune disease relief.